Left posterior inferior parietal cortex causally supports the retrieval of action knowledge - Philipp Kuhnke; Marie C. Beaupain; Vincent K.M. Cheung; Konstantin Weise; Markus Kiefer; Gesa Hartwigsen (NeuroImage, 2020)
Conceptual knowledge is central to human cognition. The left posterior inferior parietal lobe (pIPL) is implicated by neuroimaging studies as a multimodal hub representing conceptual knowledge related to various perceptual–motor modalities. However, the causal role of left pIPL in conceptual processing remains unclear. Here, we transiently disrupted left pIPL function with transcranial magnetic stimulation (TMS) to probe its causal relevance for the retrieval of action and sound knowledge. We compared effective TMS over left pIPL with sham TMS, while healthy participants performed three different tasks—lexical decision, action judgment, and sound judgment—on words with a high or low association to actions and sounds. We found that pIPL-TMS selectively impaired action judgments on low sound–low action words. For the first time, we directly related computational simulations of the TMS-induced electrical field to behavioral performance, which revealed that stronger stimulation of left pIPL is associated with worse performance for action but not sound judgments. These results indicate that left pIPL causally supports conceptual processing when action knowledge is task-relevant and cannot be compensated by sound knowledge. Our findings suggest that left pIPL is specialized for the retrieval of action knowledge, challenging the view of left pIPL as a multimodal conceptual hub.